2014
DOI: 10.1016/j.eplepsyres.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-induced disinhibition of the HPA axis increases seizure susceptibility

Abstract: Stress is the most commonly reported precipitating factor for seizures. The proconvulsant actions of stress hormones are thought to mediate the effects of stress on seizure susceptibility. Interestingly, epileptic patients have increased basal levels of stress hormones, including corticotropin-releasing hormone (CRH) and corticosterone, which are further increased following seizures. Given the proconvulsant actions of stress hormones, we proposed that seizure-induced activation of the hypothalamic-pituitary-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 50 publications
(83 reference statements)
10
84
0
Order By: Relevance
“…The stress hormone CRH was an excitatory neuropeptide with proconvulsant actions in both adult and neonatal brain, which were more sensitive to CRH (Baram and Hatalski, 1998). The production of stress hormones was mediated by the hypothalamicpituitary-adrenal (HPA) axis, involving the release of CRH from the hypothalamus (Maguire and Salpekar, 2013;O'Toole et al, 2014). There were evidences showing that CRH was released from neurosecretory nerve terminals of the paraventricular nucleus (PVN), located in the median eminence which received robust GABAergic input (Maguire and Salpekar, 2013).…”
Section: Effects Of Hypoxia-induced Neonatal Seizures On Eeg Seizuresmentioning
confidence: 98%
“…The stress hormone CRH was an excitatory neuropeptide with proconvulsant actions in both adult and neonatal brain, which were more sensitive to CRH (Baram and Hatalski, 1998). The production of stress hormones was mediated by the hypothalamicpituitary-adrenal (HPA) axis, involving the release of CRH from the hypothalamus (Maguire and Salpekar, 2013;O'Toole et al, 2014). There were evidences showing that CRH was released from neurosecretory nerve terminals of the paraventricular nucleus (PVN), located in the median eminence which received robust GABAergic input (Maguire and Salpekar, 2013).…”
Section: Effects Of Hypoxia-induced Neonatal Seizures On Eeg Seizuresmentioning
confidence: 98%
“…Interestingly, recent studies demonstrated that seizures themselves activate the HPA axis (4,8), and seizure-induced elevations in corticosterone levels correlated with increased depression-like behaviors (9). It is possible that the "first hit" alters HPA axis reactivity, whereby in response to the "second hit, " there is hyperexcitability of the HPA axis that contributes to increased seizure susceptibility and associated comorbidities.…”
Section: Primed For Problems: Stress Confers Vulnerability To Epilepsmentioning
confidence: 99%
“…Furthermore, close relationships between the sleep-wake cycle and the diurnal rhythmicity of seizure activity (Quigg, 2000), as well as between seizure susceptibility and HPA axis activity (O'Toole et al, 2014), have been found. Mostly prescribed for resynchronization of disturbed biological rhythms in a variety of pathological conditions, melatonin has low toxicity, neuroprotective effects, and a powerful antioxidant action.…”
Section: Introductionmentioning
confidence: 99%
“…i) Melatonin-mediated restoration of a disrupted hypothalamic-pituitary-adrenal axisClinical data and experimental models have shown that the HPA axis is hyperexcited in 22 epilepsy (Culebras et al, 1987;Mazarati et al, 2009;O'Toole et al, 2014) and in depression (Cai et al, 2013;Chen et al, 2015) and that melatonin can correct glucocorticoid-induced HPA axis disruption (Konakchieva et al, 1998). Because stress responses are regulated by the hypothalamic paraventicular nucleus (Laryea et al, 2013), and MT2 receptors are present in this area (Lacoste et al, 2015), we may speculate that melatonin could correct HPA axis disruption by acting on these receptors.…”
Section: Molecular Mechanisms Linking Epilepsy and Comorbid Anxiety Amentioning
confidence: 99%
See 1 more Smart Citation